Pengaruh Penerapan E-Government dan Kompetensi terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening pada Biro Organisasi Setda Provinsi Jambi - Saputra, Fadli; Syekh, Saiyid; Yamali, Fakhrul Rozi (Universitas Batanghari, 2024)
The purpose of this study is to examine how the Jambi Province Regional Secretariat Organization Bureau's implementation of e-government and competency affects worker performance, with motivation serving as an intervening variable. In this study, quantitative approaches and descriptive verification were the methodologies employed. The impact of competency and the use of e-government on worker performance at the Jambi Province Regional Secretariat Organization Bureau is the study's research topic, and motivation serves as an intervening variable. It is evident from the technique that there are 62 samples total. The PLS analysis method is applied in this study. The Jambi Province Regional Secretariat Organization Bureau's workforce competency, work motivation, and performance, as well as the e-government description, indicate that the organization's overall E-Government score is 3050 in the good category. Next, the competency variable is described as follows: with a score of 2,537, it indicates that personnel in the Jambi Province Regional Secretariat Organization Bureau have a high level of expertise. Moreover, the work motivation variable description indicates that the work motivation score falls into the High group with a value of 3588. In the meantime, the employee performance variables description indicates that the score falls into the high category at 2024. Work motivation has a positive and significant effect, competency has a significant and positive effect on work motivation, e-government has a significant effect on employee performance, competency has a negative and insignificant effect on employee performance, and work motivation has a significant and positive effect, according to the results of the Smart PLS 3.0 analysis tools. At the Jambi Province Regional Secretariat Organization Bureau, competency has a significant and positive impact on employee performance through work motivation, and e-government has a positive and significant impact on employee performance through work motivation.